Autosomal-Recessive Mutations in SLC34A1 Encoding Sodium-Phosphate Cotransporter 2A Cause Idiopathic Infantile Hypercalcemia - (:unkn) unknown (AMER SOC NEPHROLOGY, 2016)
Idiopathic infantile hypercalcemia (IIH) is characterized by severe hypercalcemia with failure to thrive, vomiting, dehydration, and nephrocalcinosis. Recently, mutations in the vitamin D catabolizing enzyme 25-hydroxyvitamin D-3-24-hydroxylase (CYP24A1) were described that lead to increased sensitivity to vitamin D due to accumulation of the active metabolite 1,25-(OH)(2)D-3. In a subgroup of patients who presented in early infancy with renal phosphate wasting and symptomatic hypercalcemia, mutations in CYP24A1 were excluded. Four patients from families with parental consanguinity were subjected to homozygosity mapping that identified a second IIH gene locus on chromosome 5q35 with a maximum logarithm of odds (LOD) score of 6.79. The sequence analysis of the most promising candidate gene, SLC34A1 encoding renal sodium-phosphate cotransporter 2A (NaPi-IIa), revealed autosomal-recessive mutations in the four index cases and in 12 patients with sporadic IIH. Functional studies of mutant NaPi-IIa in Xenopus oocytes and opossum kidney (OK) cells demonstrated disturbed trafficking to the plasma membrane and loss of phosphate transport activity. Analysis of calcium and phosphate metabolism in Slc34a1-knockout mice highlighted the effect of phosphate depletion and fibroblast growth factor-23 suppression on the development of the IIH phenotype. The human and mice data together demonstrate that primary renal phosphate wasting caused by defective NaPi-IIa function induces inappropriate production of 1,25-(OH)(2)D-3 with subsequent symptomatic hypercalcemia. Clinical and laboratory findings persist despite cessation of vitamin D prophylaxis but rapidly respond to phosphate supplementation. Therefore, early differentiation between SLC34A1 (NaPi-IIa) and CYP24A1 (24-hydroxylase) defects appears critical for targeted therapy in patients with IIH.
Keywords: HEREDITARY HYPOPHOSPHATEMIC RICKETS; GENE; IIA; NEPHROLITHIASIS; DIETARY; CYP24A1